2015
DOI: 10.1002/acr.22563
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Brachial–Ankle Pulse Wave Velocity in Patients With Takayasu Arteritis With Drug‐Eluting Stent Implantation

Abstract: Objective. This study investigates the long-term outcomes of drug-eluting stent (DES) implantation in patients with Takayasu arteritis (TAK). Methods. Data on 48 TAK patients and 40 age-, sex-, and severity-matched patients with coronary artery disease (CAD) receiving DES implantation and hospitalized in Fuwai Hospital from February 2004 to March 2014 were assessed. The clinical features, laboratory data, coronary angiographic findings, treatment, and followup outcomes were summarized retrospectively. Major ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Previous research on arterial stiffness in PMR and/or large vessel vasculitis, GCA and Takayasu's arteritis, is limited to a few studies [37][38][39][40][41][42] . In a study by Pieringer et al in 13 patients with newly diagnosed PMR and 30 agesex-matched subjects as a control group, AIx tended to be higher in the PMR group and improved significantly from 28.5 to 25.3 (p = 0.006) after 4 weeks of treatment with 25 mg/day prednisolone 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on arterial stiffness in PMR and/or large vessel vasculitis, GCA and Takayasu's arteritis, is limited to a few studies [37][38][39][40][41][42] . In a study by Pieringer et al in 13 patients with newly diagnosed PMR and 30 agesex-matched subjects as a control group, AIx tended to be higher in the PMR group and improved significantly from 28.5 to 25.3 (p = 0.006) after 4 weeks of treatment with 25 mg/day prednisolone 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The iliac region must be exposed before the femoral sensor is located on the femoral artery, in the measurement of cf-PWV. Finally, we already proved the prognostic value of ba-PWV in the patients with Takayasu Arteritis with drug-eluting stent implantation 19) . Therefore, we think ba-PWV is a more appropriate non-invasive quantification of arterial stiffness for the patients with TAK comparing with cf-PWV.…”
Section: Discussionmentioning
confidence: 80%
“…Two articles were requoted from the reference lists of eligibly identified studies. A total of 15 studies were available for the present review [13,[25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…The baPWV and cfPWV levels were significantly higher in TA patients than in controls in all the studies [25][26][27][28][29][30]. One study on crPWV showed that the TA patients in patients were higher than those in controls [26], while another did not [25].…”
Section: Pulse Wave Velocitymentioning
confidence: 98%
See 1 more Smart Citation